Leadership Style of Transformational Key User in the Success of the Implementation of Enterprise Resource Planning in the Universities in East Java, Indonesia - Wijayanto, Heri; Haryono, Tulus (Journal of Innovation in Business and Economics, 2018)
AbstractThis study is aimed to analyze to what extend is the implementation of Enterprise Resource Planning (ERP) by involving transformational key user leadership style as the moderating variable. This study used DeLone and McLean information system success model approach. There are 285 universities in east Java, Indonesia as the population. As for this study, 164 universities are chosen as the samples by using the disproportionate stratified random sampling through organizational unit analysis. The instrument that is used to analyze the data is Structural equation Modeling (SEM) program Amos 22. The constructs used to make the model are transformational key user leadership, System Quality, and User Satisfaction. The result showed that the quality system has no influence towards the user satisfaction, and transformational key user leadership style moderates the quality system influences the quality system on the user satisfaction.